Young Consumers’ Intention to Engage in The Sustainable Consumption through Sharing Economy: A Sociotechnical Approach - Qamarani, Syabibah Yusrina; Iqbal, Mohammad; Fahrudi, Agung Nugroho Luthfi Imam (Sekolah Pascasarjana Universitas Brawijaya, 2023)
The paper seeks to investigate the influences of sociotechnical aspects on young Indonesian consumers' intentions